PERIOPERATIVE OUTCOMES OF SARS-COV-2 POSITIVE PATIENTS WHO UNDERWENT URGENT AND EMERGENCY SURGERY: A RETROSPECTIVE COHORT STUDY AT A SOUTH AFRICAN QUATERNARY HOSPITAL DURING THE SARS-COV-2 PANDEMIC - baba, faheem; Bechan, Dr. Sudha; Asmal, Dr. Imraan (Student’s Journal of Health Research Africa, 2024)
Purpose This study aimed to assess the perioperative outcomes of SARS-CoV-2-positive patients undergoing urgent and emergency surgeries during the COVID-19 pandemic at a South African quaternary hospital. The primary goal was to determine whether mortality rates and complications in the local setting were consistent with global findings. Methods This retrospective review included all SARS-CoV-2-positive patients presenting for surgery from March 1, 2020, to December 28, 2021, at IALCH, Durban, South Africa. Data were extracted from electronic medical records, including demographics (age, sex, American Society of Anesthesiologists (ASA) grading, planned surgery), clinical factors (COVID diagnosis details, degree of respiratory compromise, anesthesia type), and complications. Results The major finding from the dataset was the relatively young population of the cohort, with a mean age of 32.5 years among all patients presenting for surgery. Most patients who died were classified as ASA 3 or 4, with multiple comorbidities. Multiple trauma cases were common during the study period, which coincided with a period of strict lockdown. Conclusion In this retrospective cohort study of surgical patients with confirmed SARS-CoV-2 infection, 22.8% of patients died. The findings suggest that SARS-CoV-2 may not have had a significant impact on overall all-cause mortality in this cohort. Trauma was a major contributor to mortality, particularly among ASA 3 and 4 patients.